The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms242216462
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of Transcriptome and Targeted Metabolites Identifies Key Genes Involved in Iris germanica Anthocyanin Biosynthesis

Xiaojie Zhao,
Yumeng Wu,
Xiaoyu Zhang
et al.

Abstract: The anthocyanin biosynthetic pathway is the main pathway regulating floral coloration in Iris germanica, a well-known ornamental plant. We investigated the transcriptome profiles and targeted metabolites to elucidate the relationship between genes and metabolites in anthocyanin biosynthesis in the bitone flower cultivar ‘Clarence’, which has a deep blue outer perianth and nearly white inner perianth. In this study, delphinidin-, pelargonidin-, and cyanidin-based anthocyanins were detected in the flowers. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Additionally, F3′5′H is a key gene in the delphinidin synthesis pathway. In Iris germanica , the expression of F3′5′H in the deep blue outer perianth is up-regulated, resulting in a significantly higher content of delphinidin than that in the nearly white inner perianth [ 46 ]. The results of this study showed that the F3′5′H gene was absent in P. mume , which may be an important reason for the lack of the delphinidin pathway in P. mume .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, F3′5′H is a key gene in the delphinidin synthesis pathway. In Iris germanica , the expression of F3′5′H in the deep blue outer perianth is up-regulated, resulting in a significantly higher content of delphinidin than that in the nearly white inner perianth [ 46 ]. The results of this study showed that the F3′5′H gene was absent in P. mume , which may be an important reason for the lack of the delphinidin pathway in P. mume .…”
Section: Discussionmentioning
confidence: 99%